Doping Prevention in Sport: Overview of Anti-Doping Education Programmes (Baltic Journal of Sport and Health Sciences, 2020)
Background. As doping can damage the sports industry, it is fundamental for athletes to engage in the anti-doping education programs and understand the anti-doping rules. The purpose of this article was to provide an overview of research focusing on anti-doping education.Methods. Scientific research analysis was done by focusing on doping prevention and education programs.Results. Anti-doping education should focus on young athletes, involve family members, friends and coaches. In relation with anti-doping programs which concentrated on health education and informative knowledge, moral and ethical behaviour based anti-doping education was believed to be more effective in actual doping behaviour of athletes. Since coaches could be potentially influencing athletes’ doping behaviour, there should be a collaboration of sports organizations and policy makers in order to help coaches operate within anti-doping rules by creating certain doping prevention programs.Conclusions. Research studies which examine athletes’ belief system and provoke critical thinking in athletes about using banned substances in sport might be more effective in preventing doping than programs focusing only on health education. Keywords: anti-doping, doping, education, prohibited substances.